Investigations on c-(Almost) Perfect Nonlinear Functions - Mesnager, Sihem; Riera, Constanza; Stanica, Pantelimon; Yan, Haode; Zhou, Zhengchun (IEEE transactions on information theory, 2021)
In a prior paper (Ellingsen et al. , 2020), two of us, along with P. Ellingsen, P. Felke, and A. Tkachenko, defined a new (output) multiplicative differential and the corresponding c -differential uniformity, which has the potential of extending differential cryptanalysis. Here, we continue the work by looking at some APN functions through the mentioned concept and showing that their c -differential uniformity increases significantly in some cases.